Socio-economic potential of Polish cities - a regional dimension - Bogdański, Marcin (Bulletin of Geography. Socio-economic Series, 2012)
The main aim of the research presented in this paper was to construct and evaluate a synthetic index of socio-economic potential of Polish cities (IoEp) at the level of voivodships and also to examine relations between this potential and the economic development of regions. The index reflects the level of localisation advantages offered by a city. That is why an assumption was made that there is a positive relationship between the level of socio-economic potential of cities in a region (measured by the IoEP index) and its level of economic development. The obtained results show that there are significant and stable differences in the level of economic potential of Polish cities. One can also observe that the higher the level of IoEP was, the higher the value of regional GDP per capita. That gives some basis to positively verify the research hypothesis.